2019
DOI: 10.26682/avuod.2019.22.1.20
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF CULTIVARS, PLANT SPACING AND AL-GAMIX ON GROWTH AND GREEN YIELD OF BROAD BEAN (Vicia faba L.)

Abstract: The experiment was amid to tested the effects of three Cultivars (Reina, Giza & Local), two plant spacing (15&20cm) and Al-gamix at concentration (0& 2 ml.L-1) on growth, green yield and green seed yield of Broad bean (Vicia faba.). Results showed that the cultivars had affected on vegetative, green yield and seed yield characters; The Reina cultivar had significant increase in (No. of branches , Pod Yield g. plant-1 , Total Yield ton. donum-1 , No. of seed per pod, no. of seed. Plant-1 , seed weight g, seed y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The reason of difference among faba bean cultivars in seed yield may be attributed to their genetic differences. This result is consistent with [22,23,24]. As for the interaction between phosphorus fertilization and cultivars, it had no significant effect on this trait .…”
Section: Seed Yield (Mg Ha -1 )supporting
confidence: 92%
“…The reason of difference among faba bean cultivars in seed yield may be attributed to their genetic differences. This result is consistent with [22,23,24]. As for the interaction between phosphorus fertilization and cultivars, it had no significant effect on this trait .…”
Section: Seed Yield (Mg Ha -1 )supporting
confidence: 92%
“…donum -1 and weight of 100 seed g). While the Giza cultivar significantly increased (plant high, pod length cm, pod weight g.) 4 . A study to evaluate three faba bean varieties (Gora, Moti and Degaga) found that the highest seed yield was from Degaga, Moti and Gora varieties, respectively 5 .…”
Section: Introductionmentioning
confidence: 94%
“…Eris et al [49] reported significant increases in fruit length on pepper plants (Capsicum annuum L.) treated with an extract of A. nodosum. Likewise, Ali [50] used an Ascophyllum-based product and obtained significant increases in the length of fava pods (Vicia faba L.). Aguiar [51] recorded a significant increase in the diameter of grape berries (Vitis vinifera L.) using an extract of P. calcareum-based product.…”
Section: Pods Morphologymentioning
confidence: 99%